Pengaruh Arus Kas Operasi Terhadap Pertumbuhan Laba Perusahaan Studi Kasus pada PT Multi Manunggal - Sutarti, Sutarti; Sulaeman, Adi (Jurnal Ilmiah Ranggagading (JIR), 2011)
Analysis of cash flows in line with the actual preparation of the cash flow statement also called cash flow statement. Cash flow analysis is an analysis to determine the causes of the change in the amount of cash money or to find out the sources and the use of cash during a certain period. Consolidated cash flow is considered to provide information about the ability of many companies in a profit. Cash flows from operating activities or for cash flow is derived from profit growth within a company can show earnings growth rate from year to year the company is by comparing the profits derived from the first year with the next year. The purpose of this study is to analyze the cash flow from operations to profit growth. Data collection techniques used were secondary data obtained by the corner of the Indonesia Stock Exchange in the form of financial statements of a company engaged in the food industry from the years 2005 to 2009. In this study the method used is descriptive method that aims to describe systematically and accurately about the actual facts and characteristics of the population or certain things to be studied. And analysis methods used were analysis of operating cash flow and earnings growth analysis, from such analysis can be concluded that in. Indofood Sukses Makmur Tbk. has the effect of positive operating cash flow or the very real and constant motion proportional to the company generated net income (this can be seen in the table of the percentage change between operating cash flows with net income of the company). This is caused by PT Indofood Sukses Makmur Tbk better able to create the percentage increase in operating cash flow activity. While in the PT. Unilever Indonesia Tbk has the effect of positive operating cash flow but not significantly and constantly move inversely (this can be seen in the table are percentage changes between operating cash flows with net income of the company). The Company noted that an increase in operating activities was higher than the increase in the percentage of profit generated through operations. So that it can be concluded from these data that the company was not able to create an efficient level of net income through the activities of the companys operations.